Complete Genomic Sequence of a Novel Reassortant H11N3 Influenza Virus Isolated from Domestic Ducks in Jiangsu, China - Chen, Chaoyang (American Society for Microbiology, 2012)
For the first time we report the complete genomic sequence of an H11N3 influenza virus from domestic ducks in China. Phylogenetic analysis showed that the H11N3 virus was a novel reassortant with its genes from different subtypes of domestic duck-origin avian influenza viruses, which further underlined that domestic ducks play a key role in the genetic reassortment and evolution of influenza viruses in China.